Proceedings of the Twenty-Sixth Annual ACM-SIAM Symposium on Discrete Algorithms 2014
DOI: 10.1137/1.9781611973730.66
|View full text |Cite
|
Sign up to set email alerts
|

Approximating the best Nash Equilibrium in no(log n)-time breaks the Exponential Time Hypothesis

Abstract: The celebrated PPAD hardness result for finding an exact Nash equilibrium in a two-player game initiated a quest for finding approximate Nash equilibria efficiently, and is one of the major open questions in algorithmic game theory. We study the computational complexity of finding an ε-approximate Nash equilibrium with good social welfare. Hazan and Krauthgamer and subsequent improvements showed that finding an ε-approximate Nash equilibrium with good social welfare in a two player game and many variants of th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
44
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
3
3
2

Relationship

1
7

Authors

Journals

citations
Cited by 48 publications
(45 citation statements)
references
References 20 publications
1
44
0
Order By: Relevance
“…Our result bypasses this hardness result, and obtains a PTAS for a problem for which noise-stability does not hold. Finally, we show that a PTAS for the maximum-prior problem yields a PTAS for the dual signaling problem, and we rule out the latter via a simple, clean reduction from the bestNash problem and the recent result of Braverman et al [BKW15]. This result also strengthens the hardness result from [CCD + 15] mentioned above, by showing that in the absence of noise-stability, a QPTAS is the best-possible approximation for the mixture selection problem, assuming the ETH.…”
Section: Introductionsupporting
confidence: 54%
“…Our result bypasses this hardness result, and obtains a PTAS for a problem for which noise-stability does not hold. Finally, we show that a PTAS for the maximum-prior problem yields a PTAS for the dual signaling problem, and we rule out the latter via a simple, clean reduction from the bestNash problem and the recent result of Braverman et al [BKW15]. This result also strengthens the hardness result from [CCD + 15] mentioned above, by showing that in the absence of noise-stability, a QPTAS is the best-possible approximation for the mixture selection problem, assuming the ETH.…”
Section: Introductionsupporting
confidence: 54%
“…Nash equilibria is known to be computationally hard [12,14], and in light of these findings, a considerable effort has been directed towards understanding the complexity of approximate Nash equilibrium. Results in this direction include both upper bounds [25,22,15,21,16,23,18,7,33,34,3,2] and lower bounds [20,13,9]. In particular, it is known that for a general bimatrix game an approximate Nash equilibrium can be computed in quasi-polynomial time [25].…”
Section: Related Workmentioning
confidence: 99%
“…In Section 5 we will show that the problem of approximating the best social welfare achievable by an approximate Nash equilibrium in a two-player normal form game can be written down as a constrained ǫ-ETR formula where α, γ, d, and m are constant. It has been shown that, assuming the exponential time hypothesis, this problem cannot be solved faster than quasi-polynomial time [11,19], so this also implies that constrained ǫ-ETR where α, γ, d, and m are constant cannot be solved faster than quasi-polynomial time unless the exponential time hypothesis is false.…”
Section: The Existential Theory Of the Realsmentioning
confidence: 99%